Implementation Of Government Procurement Of Goods And Services Through E-Catalogue In Micro, Small And Medium Enterprises (Msmes) In South Sumatera Province - Alfalla, M. Nur; Putra, Raniasa; Budiyanto, Muhammad Nur (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This article aims to realize good governance through e-Catalogues in micro, small, and medium enterprises (MSMEs) in South Sumatra Province. The problem focuses on how the procurement of goods and services is carried out through e-catalogues in MSMEs in South Sumatra. To address this issue, the theoretical framework of the Principles of Government Procurement of Goods and Services by Willem (2012:11-12) is utilized, which states that in good procurement of goods and services, the principles of effectiveness, efficiency, competitiveness, transparency, and accountability must be applied from the planning stage onwards. Data was collected through observation, interviews, and documentation from SMEs in South Sumatra Province and the Electronic Procurement Service (LPSE) of South Sumatra, which manages the e-catalogue in South Sumatra, and analyzed qualitatively. This study concludes that the implementation of government procurement of goods and services through the e-catalogue for micro, small, and medium enterprises (MSMEs) in South Sumatra Province is not yet optimal because it does not meet several procurement principles, namely effectiveness, efficiency, and transparency. It is hoped that in the future, the e-catalogue can be improved and continue to support the development of MSMEs.